Explore Students' Metacognitive Thinking Process in Solving Compound Polarity Problems Based on The Level of Academic Ability - Himatul Aliyah; Erman; Djoko Hartono; Husni Mubarok (Jurnal Penelitian Pendidikan IPA, 2023)
This study was designed to identify and describe students’ metacognitive thinking process in solving compound polarity based on academic ability level. Two hundred and eighty-four high school students in Indonesia participated in the study. Students are classified into high, middle and low academic ability groups based on field notes, student academic data, compound polarity problem-solving test (CPPST) scores and teacher suggestions. Six selected students from each group were designated as research subjects and then interviewed in depth to explore their metacognitive thinking processes. CPPST answer sheets and interview transcripts were analyzed using summative content analysis and tested for validity by data triangulation. The results showed that the students with high and medium academic ability level carry out metacognitive thinking processes in the dimensions of planning, monitoring and reflection in solving compound polarity problems, where the metacognitive thinking processes of students with high academic ability are more varied than students with middle academic ability. Students with low academic ability only carry out the dimensions of planning and monitoring. Therefore, teachers need to train students' metacognitive skills in solving problems and get used to applying metacognitively in each given problem solving so that students are trained to solve problems systematically, carefully and thoroughly, and manage time properly in order to obtain the expected learning achievement.